2020
DOI: 10.3390/nano10020259
|View full text |Cite
|
Sign up to set email alerts
|

Nano Zinc Oxide Induced Fetal Mice Growth Restriction, Based on Oxide Stress and Endoplasmic Reticulum Stress

Abstract: ZnO NPs have been assessed to show adverse effects on reproductive organs, but the molecular mechanisms of reproductive toxicity have not been sufficiently studied. In this research, the dosage effects from the oral exposure of ZnO NPs (30 nm) to pregnant mice in gestation day 10.5 to 17.5 was analyzed. Pregnant mice exposed to ZnO NPs induced dam injury, mice fetal growth restriction, and the fetus number decreased. The pathological evaluation showed that ZnO NPs exposure caused placental spongiotrophoblast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…In addition, there were decreased birth and weaning weights found in these pups, which was the least in BZnO-2. Chen et al, [ 11 ] supports these findings, in which they stated that the exposure to ZnONP in pregnant mice prompted dam injury, fetal growth limitation, and a decrease in the fetal numbers. They contributed to placental damage and functional alterations triggered by apoptosis, oxidative, and endoplasmic reticulum anxiety.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, there were decreased birth and weaning weights found in these pups, which was the least in BZnO-2. Chen et al, [ 11 ] supports these findings, in which they stated that the exposure to ZnONP in pregnant mice prompted dam injury, fetal growth limitation, and a decrease in the fetal numbers. They contributed to placental damage and functional alterations triggered by apoptosis, oxidative, and endoplasmic reticulum anxiety.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, the developmental toxicity of ZnONPs on the fetus also has been shown in some papers [ 10 ]. Still, preliminary studies explain its internal mechanism, as Chen et al [ 11 ] found that exposure to ZnONPs in high doses reduced the fetal number and their weight. Moreover, Teng et al [ 12 ] showed that ZnONPs affect placental weight, rat weight, and vitality.…”
Section: Introductionmentioning
confidence: 99%
“…The pregnant mice were treated with ZnO NPs at doses of 20, 60, 180, and 540 mg/kg from gestation day 10.5 to 17.5. The exposure of pregnant mice to spherical ZnO NPs leads to dam injury, fetal growth restriction, fetus number reduction and fetus body malformation ( Figure 43 ) [ 189 ]. Moreover, zinc concentration is significantly elevated in the uterus, placenta, and fetus of mice treated with 540 mg/kg ZnO NPs.…”
Section: In Vivo Animal Modelmentioning
confidence: 99%
“…The data are expressed as mean ± SD (n = 60); * p < 0.05 vs. control. Reproduced from [ 189 ] under the Creative Commons Attribution license.…”
Section: Figurementioning
confidence: 99%
“…Laboratory studies have helped to unveil the molecular mechanisms and potential therapeutics of common gestational diseases and disorders. These may include models of preeclampsia, gestational diabetes, genetic abnormalities, infections, and maternal environmental exposures (e.g., high altitude, phthalates, heavy metals, and ultrafine particles), each likely to result in the development of FGR (Yamashita et al, 2003;Arce et al, 2012;Tunster et al, 2014;Xu et al, 2016;Shen et al, 2017;Bailey et al, 2019;Morales-Rubio et al, 2019;Tachibana et al, 2019;Chen et al, 2020). It is estimated that 95% of the animals used in these studies are multiparous rodents, including mice and rats (Vandamme, 2014).…”
Section: Introductionmentioning
confidence: 99%